Manuel Moreno and the lawyers of the Argentine Confederation in the face of the British occupation of the Malvinas (1833-1834) (Quinto Sol, 2024)
Following the British occupation of the Malvinas Islands in 1833, there were different reactions among the River Plate scholars. Of these, those of Manuel Moreno, representative of the Buenos Aires government in London, are particularly well-known. However, there are no specific studies on the conceptual and argumentative differences between Moreno's defence of the sovereignty of the islands, with respect to the actions and speeches promoted by other provincial scholars. This work argues that, although the latter were based directly on the ius gentium, Moreno would appeal to uti possidetis iuris as the basis of his claims.
Keywords: occupied territory; sovereignty; ius gentium